2022
DOI: 10.3390/agriculture12081172
|View full text |Cite
|
Sign up to set email alerts
|

Modest Ag-Extension and Access to Seeds of Aromatic Rice Can Boost Returns of Smallholder Farmers in Uganda, A Case Study

Abstract: Limited farmer access to quality seeds of improved varieties and knowledge gaps in good agronomic practices are the major factors limiting rice productivity among smallholder farmers in Uganda. Promoting high yielding aromatic rice varieties alongside good agronomic practices can unlock commercial opportunities for smallholder farmers in rice cultivation, given that 80% of rice consumers in Uganda prefer aromatic rice, which is in short supply. This case study highlights a project’s achievements to accelerate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…The study's analysis revealed that the province's production of special rice and its high domestic price were influenced by high production costs [10], lack of access to quality seeds resulting to low yields [11], insufficient infrastructure such as irrigation system, storage facilities, farm-to-market roads, and equip-Open Journal of Ecology ment needed to prevent losses from exposure, pests, and natural deterioration [12] [13], high marketing costs due to rice price and road quality [14], and low consumer demand. Production costs in the Philippines were relatively higher than in Thailand and Vietnam by PHP 4 -6 per kg [15].…”
Section: Discussionmentioning
confidence: 99%
“…The study's analysis revealed that the province's production of special rice and its high domestic price were influenced by high production costs [10], lack of access to quality seeds resulting to low yields [11], insufficient infrastructure such as irrigation system, storage facilities, farm-to-market roads, and equip-Open Journal of Ecology ment needed to prevent losses from exposure, pests, and natural deterioration [12] [13], high marketing costs due to rice price and road quality [14], and low consumer demand. Production costs in the Philippines were relatively higher than in Thailand and Vietnam by PHP 4 -6 per kg [15].…”
Section: Discussionmentioning
confidence: 99%